STRATEGI KOMUNIKASI DALAM SOSIALISASI LITERASI MEDIA DI DINAS KOMUNIKASI DAN INFORMASI (DISKOMINFO) PROVINSI BALI - rosita, diana; pratiwi, nuning indah (Universitas Pendidikan Nasional, 2018)
The ability to know about the media, ranging from how we use it well and the portion would be a must for media users. The development of media is now increasing, especially social media. Media social is often used from various societies. In related to this, must have to know the restrictions in media and also important for us in receiving the information or news provided by media itself. With the easy information obtained from the media, users are reluctant to sort the information before being disseminated to other parties. The news spread out unnoticed this is what is called a hoax. To follow up the matter, the Office of Communication and Information (DISKOMINFO) of Bali Province held an activity called media literacy. In this research, the researcher tries to link the strategy that has been done by the Office of Communication and Information (DISKOMINFO) of Bali Province with six steps offered by Philip Lesly in his communication strategy which consists of, analysis & research, policy formulation, program implementation planning, communication activities, feedback, evaluation and adjustment. The Office of Communication and Information (DISKOMINFO) of Bali Province is able to implement the strategy that has been planned in accordance with the model of communication strategy that is the reference of the researcher so that the expected results can be achieved through the implementation of the strategy.KEYWOARDS : Communication Strategy of Philip Lesly, Media Literacy